Diagnostic Yield and Complications Using a 20 Gauge Prostate Biopsy Needle versus a Standard 18 Gauge Needle: A Randomized Controlled Study - wang, jianlong; Wan, Ben; Li, Chao; Wang, Jianye; Zhao, Weixin; Fu, Qiang; Zhang, Kaile (Urology Journal, 2015)
Purpose: To compare and evaluate whether a 20 gauge (20G) biopsy needle maintains a similar detection rate as that of the commonly used 18G needle for transrectal ultrasound-guided prostate biopsy (TRUSPB) aimed at assessing prostate cancer (PCa) and decreasing pain and complications. Materials and Methods: A total of 122 cases with indications of PCa were randomly allocated into two groups for this randomized controlled study. TRUSPB was performed randomly using either an 18G or 20G needle for core biopsies (62 cases with 18G and 60 cases with 20G). Detection rate, pain, and complications were assessed after the procedure. Results: The cancer detection rate in the 18G group (40.3%) did not differ from that in the 20G group (35.0%). However, the number of patients with pain was significantly lower in 20G group (P < 0.05). The number of patients with self-limiting hematuria decreased in both groups after the biopsy procedure (18G: 38 cases; 20G: 16 cases; P < .0001). Hematochezia occurred in 11 cases (9 cases [14.5%] in the 18G group; 2 cases [3.4%] in the 20G group). The number of patients with infection, dysuria, and urinary retention tended to be lower in 20G group. Conclusion: Use of a 20G needle for TRUSPB yielded a comparable cancer detection rate to that of an 18G needle and led to less local injury, pain, and complications. A larger and more sensitive study is needed to verify our results.